2000
DOI: 10.1515/cclm.2000.029
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein 90K/Mac-2BP Is an Independent Predictor of Disease Severity during Hepatitis C Virus Infection

Abstract: The serum protein designated 90K/Mac-2BP has been found at elevated concentrations in the sera of patients with various types of cancer and viral infections. The importance of the 90K/Mac-2BP serum concentrations in predicting the response towards interferon-alpha treatment for hepatitis C virus (HCV) infection prompted us to utilize a new ELISA for soluble human 90K/Mac-2BP to monitor the serum concentrations of this protein in our HCV-positive patients. Seventy HCV-PCR and anti-HCV antibody positive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…This is consistent with the findings of cross-sectional studies which showed a positive association between the 90K level and the severity of HCV infection [11,12].…”
supporting
confidence: 92%
“…This is consistent with the findings of cross-sectional studies which showed a positive association between the 90K level and the severity of HCV infection [11,12].…”
supporting
confidence: 92%
“…In addition, cells with higher expression of Mac-2BP displayed stronger adhesion to vitronectin but reduced adhesion to laminin and collagen IV, the 2 major components of basal lamina, implying that through favoring cell-cell aggregation and inhibiting cell adhesion to basal lamina, Mac-2BP maybe keep EWS cells in fluid blood circulation, where they are more prone to die, and prevent EWS cell adhesion to endothelium and extravasation (51). In liver diseases, serum 90K/Mac-2BP was found as an independent predictor of disease severity during HCV infection (52). In another report, serum Mac-2BP was evaluated in 11 chronic active hepatitis, 48 liver cirrhosis and 36 hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of these alterations in hepatitis C has been provided by Bigger et al., reporting a change in hepatic gene regulation during course and clearance of viral hepatitis C in primates [48]. Also, previous studies have associated increased serum galectin-3-binding protein levels with viral genotype 1 -4 [13, 14,16,19]. According to these findings, galectin-3-binding protein is likely a hepatitis C-specific marker of fibrosis rather than a universal fibrosis marker, despite significant increase in proteinlevel in both pathologies.…”
Section: Discussionmentioning
confidence: 97%
“…Galectin-3-binding protein is a secreted 90 kDa Nglycosylated protein with affinity for galectins as well as extracellular matrix proteins [12]. Sudden increase in serum galectin-3-binding protein levels have been reported in various infectious and cancerous diseases, including hepatitis C [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%